Industry in the Landscape, 1700-1900 - Neaverson, Peter, 1929-2005; Palmer, Marilyn, 1943- (London : Routledge, 1994)
Two hundred years of industry have transformed the British landscape. This book enables the reader to reconstruct the landscape of past industry. The authors are industrial archaeologists of national standing whose concern is to use surviving material evidence and contemporary sources to study the former working conditions of men and women. Comprehensive in coverage, the book examines fuels, metals, clothing, food, building and transport. It makes clear the tangible elements which form the basis for recreation of past landscapes and demonstrates both their function and the context in which they should be considered.
Book Cover -- Title -- Copyright -- Contents.
Industriële archeologie (rubricering Patrick Viaene)
Description based on publisher supplied metadata and other sources
Keywords: Industrial archaeology -- Great Britain; Work environment -- Great Britain -- History; Industrial archaeology ; Great Britain; Work environment ; Great Britain ; History; Electronic books; Industrial archeology - Great Britain; Work environment - Great Britain - History